Balloon anchoring to traverse the sigmoid sinus for delivery of large-caliber venous stents: A technical note. Issue 5 (October 2021) - Murakami, Tomoaki; Toyota, Shingo; Suematsu, Takuya; Wada, Yuki; Nakagawa, Kanji; Shimizu, Takeshi; Mori, Kanji; Taki, Takuyu
Background: In the reconstruction of the superior sagittal sinus or transverse sinus, it is desirable to place a large-diameter guiding catheter into the transverse sinus to introduce the stent delivery system smoothly. The utility of an anchoring technique with a percutaneous transluminal angioplasty (PTA) balloon for navigating an 8 F guiding catheter into the transverse sinus is demonstrated. Case Descriptions: Two dural arteriovenous fistula (dAVF) cases (Cognard type II a +b, Borden type II) that underwent sinus stenting are presented. In both cases, when the 8 F guiding catheter was placed in the jugular vein, the stent delivery system could not enter the transverse sinus because it could not pass through the transverse-sigmoid sinus junction. Introduction of an 8 F guiding catheter into the transverse sinus was attempted but failed. An 8-mm or 9-mm PTA balloon was used as a distal anchor, and this technique allowed easier guiding of catheter advancement into the transverse sinus. In both cases, Carotid WALLSTENTS were placed in the sinus easily, with no complications. Conclusion: Balloon anchoring in the venous system is useful for achieving large-caliber catheter access across difficult anatomy and is technically feasible.